PS-BPP06-1: ESTIMATION OF SALT INTAKE AND REMOVAL IN HEMODIALYSIS PATIENTS. (January 2023) - Ishii, Takeo; Hagiwara, Yasuhiro; Tagawa, Hitoshi; Arimura, Yoshiriro; Wakui, Hiromichi; Matsuyama, Yutaka; Tamura, Kouichi; Oyama, Kunio
Abstract : Background: Measurement of salt intake is difficult in dialysis patients, and prognosis analysis is insufficient. Recent studies have also reported that excessive salt intake leads to muscle wasting by activating the urea cycle. Hence, the removal of sodium via electrical force may lead to a favorable outcome by preventing urea cycle activation, thereby preserving tissue nutritional status, and avoiding tissue inflammation. Subject method: A cohort of 6, 883 maintenance dialysis patients was followed up for 3 years. The salt intake removal (SALT i/r) was estimated, using the formula previously reported by Watson and Ramdeen, and was classified into five groups. Statistical analysis: Cox hazard analysis, cubic spline curve for outcomes, and generalized estimation equation (GEE) were used. Results: A total of 1, 209 deaths were reported. The average baseline value of SALT i/r was 7.74 g. In the multivariate Cox hazard analysis, SALT i/r showed no correlation with all cause mortality but had significant correlation with CVD events; hazard ratio (HR) 1.02 (95% CI: 1.005 1.036). The cubic spline curves indicated that SALT i/r levels above 6.0 g decreased the risk of all cause mortality but increased the risk for CVD events and heart failure. GEE analysis suggested that baseline SALT i/r values correlated positively with time dependent serum creatinine (Cr) and CGR%. Additionally, SALT i/r values from the previous month also correlated positively with current serum Cr and CGR%. Discussion: Although a Kaplan Meier curve indicated that lower baseline salt intake caused more deaths, this may be attributed to age or malnutrition. Multivariate Cox hazard analysis showed that salt intake does not predict all cause mortality but has a positive correlation with new onset heart failure. We also described the nonlinear relationship between salt intake and risk of all cause mortality/CVD events by using cubic spline curves. This suggested that salt intake above 6 g decreased the risk of all cause mortality while increasing the risk of CVD events. In GEE, there was a significant correlation between previously measured high SALT i/r and current increase in muscle mass. Thus, we hypothesize that salt removal by dialysis without involvement of the urea cycle causally leads to muscle preservation. Conclusion: In this large cohort, estimated SALT i/r had a significant correlation with prognosis. We found that salt retention induces heart failure in dialysis patients. However, salt removal by dialysis may causally preserve tissue nutritional status.